Using an adaptive approach to making gatekeepers accountable to internally displaced persons in Mogadishu, Somalia. Issue 8 (16th November 2020) - Bryld, Erik; Kamau, Christine; Mohamoud, M. A.
ABSTRACT: Since the mid-1990s, informal power structures in the form of self-established gatekeepers have emerged within internal displacement areas in Mogadishu, Somalia. Through action research, this article explores the enhancement of accountability of these gatekeepers against the formal governance system in Mogadishu. By aligning project designs to the political economy and using a flexible approach, the driving factors of these gatekeepers' enhanced accountability can be identified. In order to contest these informal power structures, a flexible and adaptive project that constantly aligns with the local political economy offers more opportunities in enhancing accountability in difficult environments.